2009
DOI: 10.1029/2008jd011390
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble organic compounds in PM2.5 and size‐segregated aerosols over Mount Tai in North China Plain

Abstract: [1] Daytime and nighttime PM 2.5 samples were collected at the summit of Mount Tai (1534 m) located in North China Plain during a week in 2006 summer. Size-segregated aerosol particles were also collected using an eight-stage impactor during the same period. Samples were analyzed for various water-soluble organic compounds using GC/FID and GC/MS techniques. Among the species identified in PM 2.5 samples, dicarboxylic acids (C 2 -C 11 ) were found as the most abundant compound class, followed by ketocarboxylic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 63 publications
1
34
1
Order By: Relevance
“…The small peak of coarse mode of WSOC can be explained by a nature source such as pollen and soil (Fig. 9a), because water-soluble organic compounds like glucose (Graham et al, 2002;Wang et al, 2006bWang et al, , 2009Wang et al, , 2011a and humic acid (Brooks et al, 2004;Dinar et al, 2006;Havers et al, 1998) are enriched in these sources, in addition to deposition of anthropogenic pollutants onto dust. During the dust storm period WSOC still displayed a bimodal pattern, but the fine mode significantly decreased while the coarse mode sharply increased as a dominant peak.…”
Section: Size Distribution Of Wsoc Wsic and Wson In Xi'anmentioning
confidence: 99%
“…The small peak of coarse mode of WSOC can be explained by a nature source such as pollen and soil (Fig. 9a), because water-soluble organic compounds like glucose (Graham et al, 2002;Wang et al, 2006bWang et al, , 2009Wang et al, , 2011a and humic acid (Brooks et al, 2004;Dinar et al, 2006;Havers et al, 1998) are enriched in these sources, in addition to deposition of anthropogenic pollutants onto dust. During the dust storm period WSOC still displayed a bimodal pattern, but the fine mode significantly decreased while the coarse mode sharply increased as a dominant peak.…”
Section: Size Distribution Of Wsoc Wsic and Wson In Xi'anmentioning
confidence: 99%
“…Oxalate is typically the most abundant dicarboxylic acid in atmospheric aerosols and another important class of WSOC in the atmosphere (Narukawa et al, 2003). Secondary products are considered to be an important source of oxalate (Kawamura and Yasui, 2005;Wang et al, 2009). In addition to the secondary production, oxalate is emitted from vehicle exhausts (Kawamura and Kaplan, 1987), biomass burning (Narukawa et al, 1999) and biogenic activity (Kawamura et al, 1996).…”
Section: Chemical Evolutions Of Water-soluble Organic Aerosols (Oas)mentioning
confidence: 99%
“…For example, Surratt et al (2007Surratt et al ( , 2010 found that aerosol acidity can promote the formation of biogenic SOA (BSOA) derived from isoprene oxidation, such as 2-methylglyceric acid, Gly and mGly. These BSOA precursors can be further oxidized into C 2 (Meng et al, 2014;Wang et al, 2009). …”
Section: Oxalic Acid and Related Soa During The Beijing 2014 Apec Cammentioning
confidence: 99%